2020
DOI: 10.1002/app.49999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the cell structure‐impact damping relation of cross‐linked polyethylene foams by falling weight impact tests

Abstract: This study examines the effect of foam thickness on impact damping properties of closed-cell cross-linked polyethylene foams of different densities. Compression tests and falling weight impact tests were performed to detect the most important mechanisms, which affect the mechanical properties of the foams. The results showed that impact damping properties are significantly influenced by foam thickness, while energy-absorbing capability primarily depends on foam density. The average cell diameter was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…In this regard, Lyn and Mills showed that a relaxation time of 10 min between two drops is sufficient for a rebonded polyurethane foam to recover without residual deformation 81 . In contrast, in our previous study 56 on weakly crosslinked polyethylene foams, we found an opposing phenomenon. The impact tests repeated every minute resulted in a deterioration in the energy absorption and impact damping capability.…”
Section: Investigating Methods Of Polymer Foamscontrasting
confidence: 83%
See 4 more Smart Citations
“…In this regard, Lyn and Mills showed that a relaxation time of 10 min between two drops is sufficient for a rebonded polyurethane foam to recover without residual deformation 81 . In contrast, in our previous study 56 on weakly crosslinked polyethylene foams, we found an opposing phenomenon. The impact tests repeated every minute resulted in a deterioration in the energy absorption and impact damping capability.…”
Section: Investigating Methods Of Polymer Foamscontrasting
confidence: 83%
“…Once the opposite cell walls meet, the so‐called densification zone starts, where the stress level starts to increase steeply. In this case, the foam behaves as a solid polymer material 14,56,91–93 …”
Section: Investigating Methods Of Polymer Foamsmentioning
confidence: 99%
See 3 more Smart Citations